2018
DOI: 10.1259/bjr.20170834
|View full text |Cite
|
Sign up to set email alerts
|

Doses from cervical spine computed tomography (CT) examinations in the UK

Abstract: Objective: To review doses to patients undergoing cervical spine CT examinations in the UK. Methods: A data collection form was developed and distributed to medical physicists and radiographers via e-mail distribution lists. The form requested details of CT scanners, exposure protocols and patient dose index information. Results: Data were rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
1
9
0
1
Order By: Relevance
“…A Microsoft Excel TM (Washington, USA) data collection form was developed based on previous national dose audits for SPECT CT and PET CT (Iball et al 2017), and C-spine CT (Holroyd and Edyvean 2018). For each examination type the form required information on the CT scanner make, model and age.…”
Section: Data Collectionmentioning
confidence: 99%
“…A Microsoft Excel TM (Washington, USA) data collection form was developed based on previous national dose audits for SPECT CT and PET CT (Iball et al 2017), and C-spine CT (Holroyd and Edyvean 2018). For each examination type the form required information on the CT scanner make, model and age.…”
Section: Data Collectionmentioning
confidence: 99%
“…Data published by Niiniviita et al in 2018 show that the mean radiation dose of CT of the cervical spine in adult and pediatric patients of a Finnish emergency department was at an astonishing high 18.3 mGy over a 2-year period according to dose-monitoring software [ 27 ]. Data from reviewing doses to patients undergoing cervical spine CT examinations in the UK published in 2018 indicate a rounded average dose of 20 mGy for c-spine CT [ 28 ]. The mean radiation dose of our standard protocol—a protocol identical to the routine protocol in the clinical setting for c-spine trauma imaging at our department—was 12.44 ± 4.56 mGy.…”
Section: Discussionmentioning
confidence: 99%
“…According to the survey conducted in the UK in 2018, [35] the average radiation dose was CTDIvol of 20 mGy/DLP of 440 mGy·cm (the third quartile, as shown below) when standard cervical CT (tube voltage 120 kV, automatic exposure control) was mostly adopted, and it was higher than the national diagnostic reference level in 2011 (correspondingly, CTDIvol of 15 mGy/DLP of 324 mGy·cm). In the present study, the radiation dose in both HP-CT and SD-CT groups was lower than that reported by J.R. Holroyd et al [35] The radiation dose in the SD-CT (correspondingly, CTDIvol of 16 mGy/DLP of 292 mGy·cm) was close to the national diagnostic reference level in 2011, while that in the HP-CT was lower when the same or sub-optimal images were obtained. In previous studies, the repeated scan caused by various reasons and the deviation of protocol settings in cervical CT may have resulted in a higher radiation dose.…”
Section: Discussionmentioning
confidence: 99%
“…[32] However, excessive radiological examinations on cervical spines would undoubtedly increase the risk of radiation exposure, thereby dramatically raising the patient's risk of thyroid cancer. [33,34] According to the survey conducted in the UK in 2018, [35] the average radiation dose was CTDIvol of 20 mGy/DLP of 440 mGy•cm (the third quartile, as shown below) when standard cervical CT (tube voltage 120 kV, automatic exposure control) was mostly adopted, and it was higher than the national diagnostic reference level in 2011 (correspondingly, CTDIvol of 15 mGy/ DLP of 324 mGy•cm). In the present study, the radiation dose in both HP-CT and SD-CT groups was lower than that reported by J.R. Holroyd et al [35] The radiation dose in the SD-CT (correspondingly, CTDIvol of 16 mGy/DLP of 292 mGy•cm) was close to the national diagnostic reference level in 2011, while that in the HP-CT was lower when the same or sub-optimal images were obtained.…”
Section: Modelmentioning
confidence: 99%